Synthesis Of Graphene Oxides Doped Molybdenum Oxide Thin Film By Spray Pyrolysis For Carrier Selective Contact And Their Effects On Silicon Based Solar Cell Performance - Yusuf, Bashir (2022)
The carrier selective transport layer phenomenon has been successfully employed for organic heterojunction solar cells during the past three decades. Recently, the process has been transferred to silicon-based cells to achieve the same functions. The thermal evaporation technique has been used for film deposition. However, the ability to control the oxygen vacancy defect via thermal evaporation is limited, and the requirement for the deposition temperature obstructs the upscaling process to industrial mass production. This research examines the growth and characterizations of molybdenum oxide doped with graphene oxides nanostructures by spray pyrolysis technique for carrier selective transport applications. At the first stage, the influence of deposition conditions (pH solution, precursor molarity and solution flow rate) on the growth and physical properties of the MoO3 films were analyzed. The structural results showed the formation of orthorhombic lamellar growth along (0k0) orientation for all the deposition conditions. The field emission scanning electron microscopes (FESEM) confirmed pH, molarity, and solution flow rate dependence on the formation of nanobelt-like layered geometry. The EDX spectrum analysis justified the presence of O, Mo, and Si for all the growth conditions.